2021
DOI: 10.2217/bmm-2020-0418
|View full text |Cite
|
Sign up to set email alerts
|

Tp53 Rs28934571 Polymorphism Increases the Prognostic Risk in Hepatocellular Carcinoma

Abstract: Aim: Hepatocellular carcinoma (HCC) is considered to be the third leading cause of cancer death. The homologous gene of TP53 is significant in the occurrence and development of cancer. This study explored the relationship between TP53 rs28934571 polymorphism and HCC risk in Guangxi, China. Materials & methods: We first screened the association through bioinformatics. Additionally, a case–control study was performed to further verify the relationship between gene polymorphism and HCC risk after collecting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Somatic alteration analysis indicated that the mutation rates significantly differed between the three subtypes. Somatic mutations in TP53 are the most frequent alterations in human cancers, affect the progression and prognosis of HCC, and are associated with the immune microenvironment in HCC [ 27 , 28 ]. CTNNB1 mutations are also frequently found in HCC, where they promote Wnt/β-catenin pathway activation and facilitate tumor progression; therefore, CTNNB1 mutations can be used as biomarkers for evaluating immunotherapeutic effect in HCC [29] , [30] , [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Somatic alteration analysis indicated that the mutation rates significantly differed between the three subtypes. Somatic mutations in TP53 are the most frequent alterations in human cancers, affect the progression and prognosis of HCC, and are associated with the immune microenvironment in HCC [ 27 , 28 ]. CTNNB1 mutations are also frequently found in HCC, where they promote Wnt/β-catenin pathway activation and facilitate tumor progression; therefore, CTNNB1 mutations can be used as biomarkers for evaluating immunotherapeutic effect in HCC [29] , [30] , [31] .…”
Section: Discussionmentioning
confidence: 99%